Potential target for mitigation of COVID-19 by food-derived bioactive peptides - Kenji Sato (Journal of Food Bioactives, 2021)
Oral administration of food protein hydrolysate and naturally occurring peptides exert beneficial effects beyond conventional nutritional functions by supplying amino acids for protein synthesis. These peptides are referred to as food-derived bioactive peptides. The coronavirus disease 2019 (COVID-19) is caused by sever acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection. Some host and viral proteins are involved in the entry of SARS-CoV-2 into cells and their replication. Peptides with specific sequences can interact with these proteins and have potential prophylactic and therapeutic activities against COVID-19. However, it is difficult to deliver food-derived peptides to target organs without degradation by exopeptidases in the body. Alternatively, food-derived peptides and amino acid metabolites have been suggested to decrease risk factors of COVID-19 by modulating the renin-angiotensin system, the innate immune system, and the antioxidant system. This mini-review is based on in vivo responses to food-derived peptides and aims to introduce potential targets for these peptides in decreasing the risk and severity of COVID-19.